Preparation method and application of Mg-M LDHs-ZIF-67 composite film layer on surface of magnesium alloy MAO film
By forming the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy, the problem of the pores and LDHs protection effects of the microarc oxide film on the surface of the magnesium alloy is not lasting, and a more efficient corrosion protection and environmentally friendly preparation process is achieved. Improves the corrosion resistance and application range of magnesium alloys.
Patent Information
- Application Number
- CN202411372096.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The micro-arc oxide film on the surface of existing magnesium alloys has pores and microcracks, which leads to invasion of corrosive media and reduces the corrosion resistance of magnesium alloys; single LDHs and MOFs have not been long-lasting protection in the field of corrosion protection, and the preparation of raw materials is numerous, consumes a large amount and is safe. Insufficient environmental protection.
The preparation method of Mg-M LDHs@ZIF-67 composite film layer on the surface of magnesium alloy microarc oxide film is adopted. Through microarc oxidation treatment, in-situ hydrothermal reaction and coordination complexation reaction, dense Mg-M LDHs@ZIF -67 composite film layer, Mg-M LDHs nanosheets are used to fill the micropores of the MAO film, and ZIF-67 nanoparticles are filled with the sheet gap of LDHs to improve corrosion resistance.
It significantly improves the corrosion resistance and corrosion resistance of magnesium alloys, extends the service life of the film layer, simplifies the preparation process, reduces energy consumption, and has environmentally friendly and pollution-free process, which is suitable for applications in aerospace, automobiles and other fields.
Smart Images

Figure CN119243130A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface protection treatment, and specifically relates to a preparation method and application of a Mg-M LDHs@ZIF-67 composite film layer on the surface of a magnesium alloy micro-arc oxidation film (MAO). Background Art
[0002] Magnesium and magnesium alloys are the eighth largest usable element in the earth's crust, with excellent properties such as low weight, low density, high specific strength, and recyclable reuse. With the rapid development of science and technology, magnesium alloys, as a lightweight and high-strength metal with good electrical and thermal conductivity, have been widely used in aviation, automobiles, electronics and other fields. However, due to its low standard electrode potential, it is easy to corrode in water and humid environments, which makes its application very limited. At present, providing an appropriate protective film layer on the surface of magnesium alloys has become the main solution to its high corrosion rate, that is, surface treatment of magnesium alloys to improve their corrosion resistance.
[0003] Micro-arc oxidation (MAO) film has become the most common surface treatment method to improve the corrosion resistance of magnesium alloys because of its simple preparation technology and ability to form a dense ceramic layer. However, there are inherent pores and microcracks on the surface of a single MAO coating, which are formed during the discharge breakdown process of micro-arc oxidation. These micropores and cracks are channels for the corrosive medium to invade the substrate, causing the MAO film to degrade over time, thereby significantly reducing the fatigue life of the magnesium alloy. Therefore, post-treatment of the MAO film is required to improve its protective performance.
[0004] Layered Double Hydroxides (LDHs), as a new type of two-dimensional inorganic material, have been widely used in the field of corrosion protection due to their unique interlayer structure and ion exchange properties. There are many types of LDHs coatings, such as Mg-Al LDHs, Zn-Al LDHs, and Co-Al LDHs. A large number of studies have shown that they can provide good physical barriers and chemical stability for alloys. However, single LDHs have interlayer gaps, and their long-term protection effect is not ideal. In order to ensure its anti-corrosion effect, LDHs can be doped with other materials for composite growth.
[0005] Metal-organic frameworks (MOFs), three-dimensional porous materials composed of organic linkers and metal ions, are also used in the field of corrosion protection. Zeolitic imidazolate framework (ZIF) is an inorganic material with unique structure and properties. It is easy to prepare, non-toxic to the human body and the environment, and has good physical barrier and chemical stability. Therefore, it is widely used in protective coatings for magnesium alloys. Although MOFs materials have many advantages, there are still some challenges in practical applications. For example, single MOFs have a microporous / mesoporous structure, which makes them limited in their barrier properties to corrosive media. Moreover, on untreated alloy surfaces, MOFs not only cannot form films directly, but also destroy the corrosion resistance of the alloy itself. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing a Mg-M LDHs@ZIF-67 composite film on the surface of a magnesium alloy micro-arc oxidation film, aiming to solve the problems that the existing MAO has many pores, the protective effect of LDHs in the field of magnesium alloy corrosion protection is not persistent and unstable, the application of MOFs in magnesium alloy corrosion protection is not extensive, the preparation raw materials are of many types, the consumption is large, and the safety, environmental protection and energy-saving performance are poor.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a Mg-M LDHs@ZIF-67 composite film layer on the surface of a magnesium alloy MAO film comprises the following steps:
[0009] 1) immersing the magnesium alloy in a micro-arc oxidation growth solution for micro-arc oxidation treatment to obtain a magnesium alloy covered with a MAO layer;
[0010] 2) immersing the magnesium alloy coated with the MAO layer into an in-situ growth solution for in-situ hydrothermal reaction, washing and drying, and obtaining a magnesium alloy coated with a Mg-M LDHs film layer;
[0011] 3) The magnesium alloy coated with the Mg-M LDHs film layer is immersed in a ZIF-67 growth solution for coordination complex reaction, and then washed and dried to obtain a magnesium alloy coated with a Mg-M LDHs@ZIF-67 composite film layer, that is, a Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film is obtained.
[0012] In certain specific embodiments, the micro-arc oxidation growth solution includes an aqueous solution of 0.03-0.06 M trisodium phosphate dodecahydrate and 0.1-0.3 M sodium hydroxide, measured in terms of molar concentration.
[0013] In some specific embodiments, the process parameters of the micro-arc oxidation treatment are: the temperature of the micro-arc oxidation growth liquid is 5-10°C, the micro-arc oxidation treatment voltage is 300-400V, and the time is 2-8min.
[0014] In certain specific embodiments, the in-situ growth solution includes, in terms of molar concentration, 0.05-0.1 M sodium nitrate and a mixed aqueous solution of 0.1-0.2 M cobalt nitrate, 0.03-0.08 M iron nitrate, or 0.03-0.08 M aluminum nitrate.
[0015] In certain specific embodiments, the process parameters of the in-situ hydrothermal reaction are: temperature of 110-145° C., and time of 8-16 h.
[0016] In certain specific embodiments, the ZIF-67 growth solution includes a mixed aqueous solution of 0.01-0.04 M cobalt nitrate and 1.0-1.5 M dimethylimidazole, measured in terms of molar concentration.
[0017] In certain specific embodiments, the process parameters of the coordination complex reaction are: reaction temperature is room temperature of 20-30° C., and reaction time is 16-32 h.
[0018] In some specific embodiments, the magnesium alloy is also pretreated before the micro-arc oxidation treatment, specifically: the magnesium alloy substrate is polished using 150, 600, 800, 1200, and 2000# sandpapers respectively, and ultrasonically cleaned with alcohol and then dried, and then the polished magnesium alloy substrate is degreased and deoiled.
[0019] In certain specific embodiments, the degreasing and deoiling solution used in the degreasing and deoiling process is an aqueous solution including 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate, based on mass volume concentration.
[0020] The Mg-MLDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared by the aforementioned preparation method is used in the fields of aerospace, automobile, medical equipment and 3C digital.
[0021] Compared with the prior art, the present invention has at least the following advantages:
[0022] 1) The preparation method provided in the present application adopts a micro-arc oxidation growth solution with specific components, and the components are simple and easy to obtain, which greatly shortens the micro-arc oxidation treatment time to only 2-8 minutes, thereby greatly improving the production efficiency; at the same time, when preparing the Mg-M LDHs@ZIF-67 composite film layer, deionized water is used as the medium, and the magnesium matrix and the Mg in MAO are used.2+ The cation in-situ hydrothermal method is used to prepare Mg-M LDHs, which makes the preparation method of the present invention more energy-efficient and simple to operate, and provides a new technical route for industrial production.
[0023] 2) The preparation method provided by the present invention first performs micro-arc oxidation treatment on the magnesium alloy, then uses the traditional reactor one-step in-situ hydrothermal method to perform in-situ growth reaction on the magnesium alloy after micro-arc oxidation treatment, and finally obtains a uniform and dense Mg-M LDHs@ZIF-67 composite film layer through coordination complexation at room temperature; that is, the present invention combines MAO, LDHs and MOFs to prepare a composite film layer, which improves the problem that a single film layer cannot form a film / the protective performance is not durable enough, thereby improving the corrosion resistance of the magnesium alloy. The reagents used in the entire preparation process are simple, easy to obtain, and pollution-free to the environment. The reaction conditions are mild, the process is stable, and the overall process is simple and green and environmentally friendly. It can meet the needs of industrial development and mass production, and can further expand the application range of magnesium alloys.
[0024] 3) The Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared by the present invention is in-situ grown, and the prepared film layer is firmly bonded. The Mg-M LDHs film layer grown on the micro-arc oxidation film layer as the substrate is mature in technology, has low energy consumption, has good bonding force and film-forming properties, and seals the pores of the MAO film; the ZIF-67 film layer generated by the room temperature complexation reaction completely fills the pores of LDHs, making the composite film layer denser than the single MAO, LDHs, and ZIF-67 film layers, and can effectively block the invasion of corrosive media and play a role in protecting the substrate; it is suitable for promotion and application in the fields of aerospace, automobiles, medical equipment, 3C digital, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0026] Figure 1 is a scanning electron microscope photograph of the Mg-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 1;
[0027] Figure 2 is the XRD spectrum of the Mg-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 1;
[0028] Figure 3The Tafel polarization curves of AZ31 magnesium alloy, AZ31 magnesium alloy coated with MAO film, AZ31 magnesium alloy coated with Mg-Al LDHs film, AZ31 magnesium alloy coated with ZIF-67 and AZ31 magnesium alloy coated with Mg-Al LDHs@ZIF-67 composite film layer measured by electrochemical workstation in Example 1, Comparative Example 1 and Comparative Example 2 under the same coordinates;
[0029] Figure 4 is a scanning electron microscope photograph of the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 2;
[0030] Figure 5 is the XRD spectrum of the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 2;
[0031] Figure 6 are the Tafel polarization curves of the AZ31 magnesium alloy, the AZ31 magnesium alloy coated with the MAO film, and the AZ31 magnesium alloy coated with the Mg-Fe LDHs@ZIF-67 composite film at the same coordinates measured by the electrochemical workstation in Example 2;
[0032] Figure 7 is a scanning electron microscope photograph of the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 3;
[0033] Figure 8 is the XRD spectrum of the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film in Example 3;
[0034] Fig. 9 are the Tafel polarization curves of the AZ31 magnesium alloy, the AZ31 magnesium alloy coated with the MAO film, and the AZ31 magnesium alloy coated with the Mg-Co LDHs@ZIF-67 composite film at the same coordinates measured by the electrochemical workstation in Example 3;
[0035] Fig.10 The cross-sectional SEM and surface area element EDS distribution diagram of the Mg-MLDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1-3;
[0036] Fig.11 The durability test results of the Mg-MLDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1-3 are Tafel polarization curves at the same coordinates after the composite film layer was immersed in a 3.5wt% NaCl solution for 14 days. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0038] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0039] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0040] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0041] In the following examples, cobalt nitrate, sodium nitrate, ferric nitrate, aluminum nitrate, anhydrous ethanol, and deionized water were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., China;
[0042] In the following examples, the corrosion resistance is reflected by testing the Tafel polarization curve of each test sample.
[0043] Example 1
[0044] The method for preparing the Mg-Al LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film provided in this embodiment comprises the following steps:
[0045] 1) Preprocessing
[0046] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0047] 12) Grinding: Grind the AZ31 magnesium alloy using 150#, 600#, 800#, 1200#, and 2000# sandpapers respectively, and ultrasonically clean the alloy with alcohol for five minutes and then dry it for later use;
[0048] 13) The polished AZ31 magnesium alloy was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature of 25°C for 2 minutes; then washed once with deionized water and dried with cold air;
[0049] 2) Micro-arc oxidation film (MAO film for short)
[0050] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0051] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction is performed for 5 minutes to obtain a magnesium alloy covered with a MAO film;
[0052] 3) In situ growth of Mg-Al LDHs film
[0053] 31) According to the molar concentration, sodium nitrate and aluminum nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M and the molar concentration of aluminum nitrate is 0.05 M; and then the pH value thereof is adjusted to 10.72 using a 0.1 M NaOH aqueous solution;
[0054] 32) placing the magnesium alloy coated with the MAO film prepared in step 2) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 31) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ hydrothermal reaction growth at a reaction temperature of 120° C. for a reaction time of 12 h, washing and drying to obtain a magnesium alloy coated with a Mg-Al LDHs film;
[0055] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Mg-Al LDHs film layer after the reaction in step 3) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Mg-Al LDHs film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0056] 4) Coordination complex growth of ZIF-67 membrane
[0057] 41) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0058] 42) The magnesium alloy coated with the Mg-Al LDHs film layer prepared in step 3) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, washed and dried to obtain a magnesium alloy coated with a Mg-Al LDHs@ZIF-67 composite film layer; washed with deionized water, and dried to obtain a Mg-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film.
[0059] The present application tests the morphology, structure and performance of the Mg-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in this embodiment, specifically:
[0060] 1) Appearance
[0061] The present application conducted an appearance morphology test on the Mg-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy in Example 1. The electron microscope scanning image is shown in FIG. Figure 1 As shown in the figure, it can be seen that the Mg-Al LDHs nanosheets grown on the surface of the magnesium alloy MAO film grow in multiple directions, and there are small pores between the sheets; after the growth of the Mg-Al LDHs@ZIF-67 composite film layer, the LDHs nanosheets have been completely covered, and the ZIF-67 nanoparticles on the surface grow into a film, and the density of the composite film layer is significantly improved.
[0062] 2) Structural analysis
[0063] The present application tests the crystallinity of the Mg-Al LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film in Example 1. The XRD spectrum is as follows: Figure 2 As shown in the figure, (003) and (006) crystal planes are characteristic crystal planes of LDHs. It can be seen from the figure that the Mg-Al LDHs coating has been successfully prepared. The diffraction peaks of the Mg-Al LDHs@ZIF-67 composite coating at 7.31°, 10.36°, 12.72°, 14.40°, 16.45° and 18.04° correspond to the (011), (002), (112), (013), (022) and (222) crystal planes of ZIF-67, respectively, indicating that it has good crystallinity.
[0064] 3) Electrochemical performance
[0065] The present application tests the electrochemical properties of the magnesium alloy surface film layer in Example 1 by an electrochemical workstation. In addition, the electrochemical properties of Comparative Example 1 and Comparative Example 2 are used for comparison, specifically:
[0066] The Tafel polarization curves of AZ31 magnesium alloy, magnesium alloy coated with MAO film (curve MAO), magnesium alloy coated with Mg-AlLDHs film (curve Mg-Al LDHs), magnesium alloy coated with ZIF-67 film (curve ZIF-67) and magnesium alloy coated with Mg-AlLDHs@ZIF-67 composite film (curve Mg-Al LDHs@ZIF-67) under the same coordinates measured by electrochemical workstation are as follows: Figure 3 Specifically:
[0067] The corrosion resistance test of the magnesium alloy protective film is represented by the electrochemical polarization curve (the equipment model is Princeton4000A), in which the corrosion voltage of the AZ31 magnesium alloy is -1.37V, the corrosion voltage of the AZ31 magnesium alloy coated with the Mg-Al LDHs film after the treatment of the comparative example 1 is -1.28V, the corrosion voltage of the AZ31 magnesium alloy coated with the ZIF-67 film after the treatment of the comparative example 2 is -1.49V, the corrosion voltage of the AZ31 magnesium alloy coated with the MAO film after the treatment of the embodiment 1 is -1.55V, and the corrosion voltage of the AZ31 magnesium alloy coated with the Mg-Al LDHs@ZIF-67 composite film is -1.25V, which is higher than the corrosion voltage of the magnesium alloy substrate and the corrosion tendency is reduced. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of pure AZ31 magnesium alloy is 1.02×10 -5 Acm -2 The corrosion current density of the AZ31 magnesium alloy coated with Mg-Al LDHs film after treatment under the conditions of Comparative Example 1 is 1.27×10 -7 A cm -2 The corrosion current density of the AZ31 magnesium alloy coated with ZIF-67 film after treatment under the conditions of Comparative Example 2 is 7.44×10 -4 A cm -2 However, the corrosion current density of the magnesium alloy coated with MAO film after treatment under the conditions of Example 1 is 3.86×10 -6 A cm -2 The corrosion current density of the magnesium alloy coated with Mg-Al LDHs@ZIF-67 composite film is 8.58×10 -9 A cm -2. Compared with the sample of AZ31 magnesium alloy, the corrosion current density is reduced by 4 orders of magnitude; compared with the magnesium alloy coated with MAO film, the corrosion current density is reduced by 3 orders of magnitude; compared with the magnesium alloy coated with Mg-Al LDHs film, the corrosion current density is reduced by 2 orders of magnitude; compared with the magnesium alloy coated with ZIF-67 film, the corrosion current density is reduced by 5 orders of magnitude. What is special is that the electrochemical performance of the ZIF-67 film on the surface of the magnesium alloy is one order of magnitude higher than that of the untreated AZ31 substrate. This is because it is difficult for ZIF-67 nanoparticles to form a film on the surface of the magnesium alloy, and a small amount of aggregated nanoparticles become the invasion point of the corrosive medium. Therefore, the MOFs film layer cannot exist alone on the surface of the magnesium alloy. The above results can fully illustrate that the Mg-Al LDHs@ZIF-67 composite film has an effective corrosion inhibition effect on the AZ31 magnesium alloy, and it has better corrosion resistance than the single MAO, LDHs and ZIF-67 films. The Mg-Al LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film of the present invention has excellent corrosion resistance and can effectively protect the magnesium substrate.
[0068] Example 2
[0069] The method for preparing the Mg-Fe LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film provided in this embodiment comprises the following steps:
[0070] 1) Preprocessing
[0071] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0072] 12) Magnesium alloy pretreatment: AZ31 magnesium alloy was polished with 150#, 600#, 800#, 1200#, and 2000# sandpaper, and ultrasonically cleaned with alcohol for five minutes and then dried for use;
[0073] 13) The polished AZ31 magnesium alloy was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature of 25°C for 2 minutes; then washed once with deionized water and dried with cold air;
[0074] 2) Micro-arc oxidation film (MAO film for short)
[0075] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0076] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a magnesium alloy covered with a MAO film;
[0077] 3) In situ growth of Mg-Fe LDHs film
[0078] 31) According to the molar concentration, sodium nitrate and ferric nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M and the molar concentration of ferric nitrate is 0.01 M; and then the pH value thereof is adjusted to 12 using a 0.1 M NaOH aqueous solution;
[0079] 32) placing the magnesium alloy coated with the MAO film prepared in step 2) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 31) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ hydrothermal reaction growth at a reaction temperature of 120° C. for a reaction time of 12 h, washing and drying to obtain a magnesium alloy coated with a Mg-Fe LDHs film;
[0080] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Mg-Fe LDHs film layer after the reaction in step 3) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Mg-Fe LDHs film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0081] 4) Coordination complex growth of ZIF-67 membrane
[0082] 41) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0083] 42) The magnesium alloy coated with the Mg-Fe LDHs film layer prepared in step 3) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, and then washed and dried to obtain a magnesium alloy coated with a Mg-Fe LDHs@ZIF-67 composite film layer; washed with deionized water and dried to obtain a Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film.
[0084] The present application tests the morphology, structure and performance of the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in this embodiment, specifically:
[0085] 1) Appearance
[0086] The present application conducted an appearance morphology test on the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 2. The electron microscope scanning image is shown in FIG. Figure 4 As shown in the figure, it can be seen that the Mg-Fe LDHs nanosheets grown on the surface of the magnesium alloy MAO film are larger in size, but the sheets are thin and knife-shaped; after the Mg-Fe LDHs@ZIF-67 composite film layer is grown, the LDHs nanosheets have been completely covered, and the ZIF-67 nanoparticles on the surface are of different sizes and there are pores between them, but the composite film layer completely improves its surface morphology.
[0087] 2) Structural analysis
[0088] The present application tests the crystallinity of the Mg-Fe LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film in Example 2. The XRD spectrum is shown in FIG. Figure 5 As shown in the figure, (003) and (006) crystal planes are characteristic crystal planes of LDHs. It can be seen from the figure that the Mg-Fe LDHs coating has been successfully prepared. The diffraction peaks of the Mg-Fe LDHs@ZIF-67 composite coating at 7.31°, 10.36°, 12.72°, 14.40°, 16.45° and 18.04° correspond to the (011), (002), (112), (013), (022) and (222) crystal planes of ZIF-67, respectively, indicating that it has good crystallinity.
[0089] 3) Electrochemical performance
[0090] The present application tests the electrochemical properties of the magnesium alloy surface film layer in Example 2 by using an electrochemical workstation, specifically:
[0091] The Tafel polarization curves of AZ31 magnesium alloy, magnesium alloy coated with MAO film (curve MAO) and magnesium alloy coated with Mg-Fe LDHs@ZIF-67 composite film (curve Mg-Fe LDHs@ZIF-67) at the same coordinates measured by electrochemical workstation are as follows: Figure 6 As shown, specifically:
[0092] The corrosion resistance test of the magnesium alloy protective film is represented by the electrochemical polarization curve (equipment model is Princeton4000A), in which the corrosion voltage of AZ31 magnesium alloy is -1.37V, the corrosion voltage of AZ31 magnesium alloy coated with MAO film after treatment under the conditions of Example 2 is -1.55V, and the corrosion voltage of AZ31 magnesium alloy coated with Mg-Fe LDHs@ZIF-67 composite film is -1.38V, which is equivalent to the corrosion voltage of magnesium alloy substrate. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of pure AZ31 magnesium alloy is 1.02×10 -5 Acm -2 The corrosion current density of the magnesium alloy covered with MAO film is 3.86×10 -6 A cm -2 However, the corrosion current density of the magnesium alloy coated with the Mg-Fe LDHs@ZIF-67 composite film after treatment under the conditions of Example 2 is 7.41×10 -8 A cm -2 The corrosion current density of the treated magnesium alloy is reduced by 2 orders of magnitude compared with the magnesium alloy coated with MAO film; the corrosion current density is reduced by 3 orders of magnitude compared with the sample of AZ31 magnesium alloy. The above results can fully illustrate that the Mg-Fe LDHs@ZIF-67 composite film has an effective corrosion inhibition effect on AZ31 magnesium alloy, and the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film of the present invention has excellent corrosion resistance and can effectively protect the magnesium substrate.
[0093] Example 3
[0094] The method for preparing the Mg-Co LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film provided in this embodiment comprises the following steps:
[0095] 1) Preprocessing
[0096] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0097] 12) Magnesium alloy pretreatment: grinding the AZ31 magnesium alloy with 150#, 600#, 800#, 1200#, and 2000# sandpapers, ultrasonically cleaning with alcohol for five minutes, and drying for standby use;
[0098] 13) The polished AZ31 magnesium alloy was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0099] 2) Micro-arc oxidation film (MAO film for short)
[0100] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0101] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a MAO layer on the surface of the magnesium alloy;
[0102] 3) In situ growth of Mg-Co LDHs film
[0103] 31) According to the molar concentration, sodium nitrate and cobalt nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M and the molar concentration of cobalt nitrate is 0.02 M; and then the pH value thereof is adjusted to 10.5 using a 0.1 M NaOH aqueous solution;
[0104] 32) Putting the magnesium alloy coated with MAO film prepared in step 2) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 31) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ hydrothermal reaction at a reaction temperature of 135° C. for a reaction time of 12 h, washing and drying to obtain a magnesium alloy coated with Mg-Co LDHs film;
[0105] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Mg-Co LDHs film layer after the reaction in step 3) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Mg-Co LDHs film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0106] 4) Coordination complex growth of ZIF-67 membrane
[0107] 41) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0108] 42) The magnesium alloy coated with the Co-Ni LDHs film layer prepared in step 3) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, and then washed and dried to obtain a magnesium alloy coated with a Mg-Co LDHs@ZIF-67 composite film layer; washed with deionized water and dried to obtain a Mg-Co LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film.
[0109] The present application tests the morphology, structure and performance of the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in this embodiment, specifically:
[0110] 1) Appearance
[0111] The present application conducted an appearance morphology test on the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film in Example 3. The electron microscope scanning image is shown in FIG. Figure 7 As shown in the figure, it can be seen that the Mg-Co LDHs nanosheets grown on the surface of the magnesium alloy MAO film are small in size, slightly curled, and have tiny holes; after the Mg-Co LDHs@ZIF-67 composite film layer is grown, the LDHs nanosheets are obviously covered, the ZIF-67 nanoparticles on the surface are uniform in size and connected into sheets, and the density of the composite film layer is significantly improved.
[0112] 2) Structural analysis
[0113] The present application tests the crystallinity of the Mg-Co LDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc oxidation film in Example 3. The XRD spectrum is shown in FIG. Figure 8 As shown in the figure, (003) and (006) crystal planes are the characteristic crystal planes of LDHs. It can be seen from the figure that the Mg-Co LDHs coating has been successfully prepared. The diffraction peaks of the Mg-Co LDHs@ZIF-67 composite coating at 7.31°, 10.36°, 12.72°, 14.40°, 16.45° and 18.04° correspond to the (011), (002), (112), (013), (022) and (222) crystal planes of ZIF-67, respectively, indicating that it has good crystallinity.
[0114] 3) Electrochemical performance
[0115] The present application tests the electrochemical properties of the magnesium alloy surface film layer in Example 3 by using an electrochemical workstation, specifically:
[0116] The Tafel polarization curves of AZ31 magnesium alloy, magnesium alloy coated with MAO film (curve MAO) and magnesium alloy coated with Mg-Co LDHs@ZIF-67 composite film (curve Mg-Co LDHs@ZIF-67) at the same coordinates measured by electrochemical workstation are as follows: Fig. 9 As shown, specifically:
[0117] The corrosion resistance test of the magnesium alloy protective film is represented by the electrochemical polarization curve (equipment model is Princeton4000A), in which the corrosion voltage of AZ31 magnesium alloy is -1.37V, the corrosion voltage of AZ31 magnesium alloy coated with MAO film after treatment under the conditions of Example 3 is -1.55V, and the corrosion voltage of AZ31 magnesium alloy coated with Mg-Co LDHs@ZIF-67 composite film is -0.90V, which is significantly improved compared with the corrosion voltage of magnesium alloy substrate, and the corrosion tendency is reduced. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of pure AZ31 magnesium alloy is 1.02×10 -5 Acm -2 The corrosion current density of the magnesium alloy covered with MAO film is 3.86×10 -6 A cm -2 However, the corrosion current density of the sample coated with Mg-CoLDHs@ZIF-67 composite film after treatment under the conditions of Example 3 is 2.81×10 -9 A cm -2 The corrosion current density of the treated samples was reduced by 3 orders of magnitude compared with the magnesium alloy coated with MAO film; and by 4 orders of magnitude compared with the sample of AZ31 magnesium alloy. The above results fully demonstrate that the Mg-Co LDHs@ZIF-67 composite film has an effective corrosion inhibition effect on AZ31 magnesium alloy, and the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy micro-arc oxidation film of the present invention has excellent corrosion resistance and can effectively protect the magnesium substrate.
[0118] Comparative Example 1
[0119] The preparation method of the LDHs film on the surface of the magnesium alloy provided in this comparative example is basically the same as that in Example 1, except that the preparation method directly performs in-situ growth of the Mg-Al LDHs film on the surface of the pretreated magnesium alloy, and specifically comprises the following steps:
[0120] 1) Preprocessing
[0121] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0122] 12) Magnesium alloy pretreatment: grinding the AZ31 magnesium alloy with 150#, 600#, 800#, 1200#, and 2000# sandpapers, ultrasonically cleaning with alcohol for five minutes, and drying for standby use;
[0123] 13) The polished AZ31 magnesium alloy was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0124] 2) In situ growth of Mg-Al LDHs film
[0125] 21) According to the molar concentration, sodium nitrate and aluminum nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M and the molar concentration of aluminum nitrate is 0.05 M; and then the pH value thereof is adjusted to 10.72 using a 0.1 M NaOH aqueous solution;
[0126] 22) The degreased and deoiled magnesium alloy prepared in step 1) is placed in a polytetrafluoroethylene liner sleeve, and then the in-situ growth liquid prepared in step 21) is poured in and the liner is placed in a reactor, tightened, and finally placed in a drying oven for in-situ growth, the reaction temperature is 120°C, the reaction time is 12h, and then washed and dried to obtain a magnesium alloy sample covered with a Mg-Al LDHs film;
[0127] The cleaning and drying is specifically to first use running deionized water to clean the magnesium alloy sample covered with the Mg-Al LDHs film layer after the reaction in step 2) to remove the in-situ growth liquid attached to the surface, then put it into an ultrasonic cleaning machine in anhydrous ethanol for ultrasonic cleaning for 3 minutes, then clean it with deionized water, and dry it to obtain the Mg-Al LDHs film layer on the surface of the magnesium alloy;
[0128] Comparative Example 2
[0129] The preparation method of ZIF-67 on the surface of magnesium alloy provided in this comparative example is basically the same as that in Example 1, except that the preparation method directly performs coordination complex growth of ZIF-67 film on the surface of pretreated magnesium alloy, which comprises the following steps:
[0130] 1) Degreasing and oil removal
[0131] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0132] 12) Pretreatment of magnesium alloy: using 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and using alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0133] 13) The polished AZ31 magnesium alloy was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0134] 2) Coordination complex growth of ZIF-67
[0135] 21) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0136] 22) The degreased and deoiled magnesium alloy prepared in step 1) is immersed in a mixed solution of the above two aqueous solutions, maintained at room temperature 25°C for 25 hours for coordination and complexation, washed and dried to obtain a magnesium alloy coated with ZIF-67; washed with deionized water and dried to obtain a ZIF-67 sample on the surface of the magnesium alloy.
[0137] Comparative Example 3
[0138] The preparation method of the ZIF-67@Mg-M LDHs composite film layer on the surface of the magnesium alloy micro-arc oxidation film provided in this comparative example is basically the same as that of Examples 1-3, except that the film preparation sequence on the surface of the MAO film is changed, and the ZIF-67 film is prepared first, and then the Mg-M LDHs is prepared, specifically:
[0139] 1) Preprocessing
[0140] 11) preparing an aqueous solution containing 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate;
[0141] 12) Pretreatment of magnesium alloy: using 150#, 600#, 800#, 1200#, and 2000# sandpaper to grind the magnesium alloy, and using alcohol to ultrasonically clean it for five minutes and then dry it for use;
[0142] 13) The polished magnesium alloy AZ31 was immersed in the above-mentioned degreasing and deoiling aqueous solution, kept in a water bath at 50°C for 60 seconds, then alkaline washed with a 1M sodium hydroxide aqueous solution for 30 seconds, and then polished with 400g / L nitric acid (ρ=1.42g / ml) at room temperature 25°C for 2 minutes; then rinsed once with deionized water and blown dry with cold air.
[0143] 2) Micro-arc oxidation film (MAO film for short)
[0144] 21) Prepare a micro-arc oxidation growth solution containing 0.049 M trisodium phosphate dodecahydrate and 0.18 M sodium hydroxide using deionized water according to the molar concentration;
[0145] 22) First, the magnesium alloy sample after degreasing and deoiling in step 1) is fixed in a polymethyl methacrylate electrolytic cell equipped with a stainless steel plate by copper wire, and then the micro-arc oxidation growth solution in step 21) is poured; the anode is AZ31 magnesium alloy, and the cathode is a stainless steel plate; the temperature of the micro-arc oxidation growth solution is 8°C, the reaction voltage is 350V, and the reaction time is 5min, to obtain a magnesium alloy covered with a MAO film;
[0146] 3) Coordination complex growth of ZIF-67 membrane
[0147] 31) Prepare two aqueous solutions containing 0.02 M cobalt nitrate and 1.4 M dimethylimidazole respectively;
[0148] 32) Soaking the magnesium alloy coated with the MAO film prepared in step 2) in a mixed solution of the above two aqueous solutions, maintaining it at room temperature of 25° C. for 25 hours for coordination and complexation, washing and drying to obtain a magnesium alloy coated with a ZIF-67 film; washing it with deionized water, and drying it to obtain a ZIF-67 film on the surface of the magnesium alloy micro-arc oxidation film;
[0149] 4) In situ growth of ZIF-67@Mg-M LDHs membrane
[0150] 41) According to the molar concentration, sodium nitrate, cobalt nitrate / aluminum nitrate / ferric nitrate are dissolved in deionized water and mixed evenly to obtain an in-situ growth solution; wherein the molar concentration of sodium nitrate is 0.1 M, the molar concentration of cobalt nitrate is 0.15 M, and the molar concentrations of aluminum nitrate and ferric nitrate are 0.05 M; and then the pH values thereof are adjusted to 10.72, 12, and 10.5 respectively using a 0.1 M NaOH aqueous solution;
[0151] 42) placing the magnesium alloy coated with the ZIF-67 film prepared in step 3) into a polytetrafluoroethylene liner sleeve, then pouring the in-situ growth solution prepared in step 41) into the liner and placing the liner into the reactor, tightening it, and finally placing it in a drying oven for in-situ growth at a reaction temperature of 125° C. for a reaction time of 12 h, washing and drying to obtain magnesium alloys coated with ZIF-67@Mg-Al LDHs, ZIF-67@Mg-Fe LDHs, and ZIF-67@Mg-Co LDHs films;
[0152] The cleaning and drying are as follows: the magnesium alloy sample covered with the ZIF-67@Mg-M LDHs film layer after the reaction in step 4) is first cleaned with flowing deionized water to remove the in-situ growth liquid attached to the surface, and then ultrasonically cleaned in anhydrous ethanol for 3 minutes using an ultrasonic cleaning machine, and then cleaned with deionized water and dried to obtain a ZIF-67@Mg-M LDHs composite film layer on the surface of the magnesium alloy micro-arc oxidation film;
[0153] The present application conducted an XRD test on the ZIF-67@Mg-MLDHs composite film layer on the surface of the magnesium alloy micro-arc oxidation film prepared in Comparative Example 3 and found that the characteristic diffraction peaks of ZIF-67 in the ZIF-67@Mg-M composite film layer had basically disappeared, that is to say, the ZIF-67 structure in the composite film layer had been destroyed. Therefore, the method of first preparing ZIF-67 and then preparing LDHs on the surface of the magnesium alloy MAO film cannot make the two structures of ZIF-67 and LDHs coexist, and therefore is not universal.
[0154] In addition, the present application also observed the cross-sectional thickness and surface element distribution of the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1, 2 and 3 by SEM and EDS. The results are as follows: Fig.10 As shown in the figure, it can be seen that when a single MAO layer is formed on the surface of the magnesium alloy, its thickness is 3.18±0.28μm; the thickness of the Mg-Al LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy in Example 1 is 5.03±0.17μm; the thickness of the Mg-Fe LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy in Example 2 is 5.09±0.22μm; the thickness of the Mg-Co LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy in Example 3 is 7.27±0.22μm; Therefore, the Mg-MLDHs@ZIF-67 composite film layer on the surface of the MAO film of the magnesium alloy obtained by the preparation method of the present application, that is, the Mg-M LDHs@ZIF-67 composite film layer on the surface of the micro-arc oxidation film of the magnesium alloy prepared by the preparation method of the present application The thickness of the LDHs@ZIF-67 composite film layer is relatively thin. On the basis of the original MAO film layer, without significantly increasing the total thickness of the composite film, the composite film layer is prepared by combining MAO, LDHs and MOFs, which synergistically improves the corrosion resistance of the magnesium alloy.
[0155] Furthermore, the present application also tests the durability of the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared in Examples 1, 2 and 3 by an electrochemical workstation. The specific test method is to immerse the composite film layer in a 3.5wt% NaCl solution for 14 days and then detect its Tafel polarization curve by an electrochemical workstation; the test results are as follows: Fig.11As shown in the figure, the corrosion voltage of the AZ31 magnesium alloy coated with MAO film after immersion for 14 days is -1.46V, the corrosion voltage of the AZ31 magnesium alloy coated with Mg-Al LDHs@ZIF-67 composite film after immersion for 14 days after treatment under the conditions of Example 1 is -1.40V, the corrosion voltage of the AZ31 magnesium alloy coated with Mg-Fe LDHs@ZIF-67 composite film after immersion for 14 days after treatment under the conditions of Example 2 is -1.45V, and the corrosion voltage of the AZ31 magnesium alloy coated with Mg-Co LDHs@ZIF-67 composite film after immersion for 14 days after treatment under the conditions of Example 3 is -1.45V. The corrosion rate and corrosion resistance are directly related to the corrosion current density. The corrosion current density of the magnesium alloy coated with MAO film after immersion for 14 days is 4.76×10 -5 A cm -2 The corrosion current density of the magnesium alloy coated with the Mg-Al LDHs@ZIF-67 composite film after immersion for 14 days was 4.19×10 -7 Acm -2 The corrosion current density of the magnesium alloy coated with the Mg-Fe LDHs@ZIF-67 composite film after immersion for 14 days was 4.36×10 -6 A cm -2 The corrosion current density of the magnesium alloy coated with the Mg-Co LDHs@ZIF-67 composite film after immersion for 14 days was 1.30×10 -7 A cm -2 Compared with the magnesium alloy coated with MAO film after immersion for 14 days, the corrosion current density is reduced by 2 orders of magnitude. The above results can fully demonstrate that the Mg-MLDHs@ZIF-67 composite film has excellent durability and long-term effective corrosion inhibition on AZ31 magnesium alloy. It has better corrosion resistance than single MAO, LDHs and ZIF-67 films, and can effectively protect the magnesium matrix.
[0156] In summary, the preparation method of the Mg-MLDHs@ZIF-67 composite film on the surface of the magnesium alloy micro-arc film provided by the present invention is based on the magnesium alloy MAO film and makes full use of the large amount of Mg in the magnesium alloy matrix and the MAO film. 2+Mg-M LDHs film was grown in situ by hydrothermal method, and then Mg-M LDHs@ZIF-67 composite film was obtained by coordination reaction. The micropores of MAO were filled with Mg-MLDHs nanosheets, and the interlaminar gaps of LDHs were filled with ZIF-67 nanoparticles, making the composite film more compact and more corrosion resistant. In addition, due to the in-situ growth, the Mg-M LDHs@ZIF-67 composite film was directly formed on the surface of the magnesium alloy MAO film, which improved the bonding strength and film-forming performance between the film and the substrate, and improved the feasibility of application in the industrial field. The Mg-M LDHs@ZIF-67 composite film not only closed the pores of the MAO film, but also had the characteristics of corrosion resistance. Its performance is far better than that of the untreated AZ31 magnesium alloy, and better than any single magnesium alloy surface corrosion protection film. After a large number of experiments, the inventors found that by using a traditional mature reactor on the MAO membrane layer, the purpose can be achieved through hydrothermal reaction and room-temperature complex reaction, thereby generating a Mg-MLDHs@ZIF-67 composite membrane layer with good bonding strength and good corrosion resistance; the present invention has simple operating steps, environmentally friendly and non-toxic raw materials, and a short time consumption. Only a trace amount of external elements is required to obtain a Mg-M LDHs@ZIF-67 composite membrane layer with better effect, and lower energy consumption.
[0157] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a Mg-M LDHs@ZIF-67 composite film layer on the surface of a magnesium alloy MAO film, characterized in that: The steps include: 1) immersing the magnesium alloy in a micro-arc oxidation growth solution for micro-arc oxidation treatment to obtain a magnesium alloy covered with a MAO layer; 2) immersing the magnesium alloy coated with the MAO layer into an in-situ growth solution for in-situ hydrothermal reaction, washing and drying, and obtaining a magnesium alloy coated with a Mg-M LDHs film layer; 3) The magnesium alloy coated with the Mg-M LDHs film layer is immersed in a ZIF-67 growth solution for coordination complex reaction, and then washed and dried to obtain a magnesium alloy coated with a Mg-M LDHs@ZIF-67 composite film layer, that is, a Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film is obtained.
2. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 1, characterized in that: In terms of substance concentration, the micro-arc oxidation growth solution includes an aqueous solution of 0.03-0.06 M trisodium phosphate dodecahydrate and 0.1-0.3 M sodium hydroxide.
3. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 2, characterized in that: The process parameters of the micro-arc oxidation treatment are: the temperature of the micro-arc oxidation growth liquid is 5-10° C., the micro-arc oxidation treatment voltage is 300-400 V, and the time is 2-8 min.
4. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 1, characterized in that: In terms of molar concentration, the in-situ growth solution includes 0.05-0.1M sodium nitrate and a mixed aqueous solution of 0.1-0.2M cobalt nitrate, 0.03-0.08M iron nitrate or 0.03-0.08M aluminum nitrate.
5. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 4, characterized in that: The process parameters of the in-situ hydrothermal reaction are: temperature of 110-145° C. and time of 8-16 h.
6. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 1, characterized in that: In terms of molar concentration, the ZIF-67 growth solution includes a mixed aqueous solution of 0.01-0.04 M cobalt nitrate and 1.0-1.5 M dimethylimidazole.
7. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 6, characterized in that: The process parameters of the coordination complex reaction are: reaction temperature is room temperature of 20-30° C., and reaction time is 16-32 hours.
8. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 1, characterized in that: The method also includes pre-treatment of the magnesium alloy before micro-arc oxidation treatment, specifically: grinding the magnesium alloy substrate with 150, 600, 800, 1200, and 2000# sandpaper respectively, ultrasonically cleaning with alcohol and then drying, and then degreasing and deoiling the ground magnesium alloy substrate.
9. The method for preparing the Mg-M LDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film according to claim 8, characterized in that: The degreasing and oil removal solution used in the degreasing and oil removal process is an aqueous solution including 40 g / L of sodium hydroxide, 25 g / L of sodium carbonate, and 40 g / L of sodium phosphate, based on mass volume concentration.
10. Application of the Mg-MLDHs@ZIF-67 composite film layer on the surface of the magnesium alloy MAO film prepared by the preparation method according to any one of claims 1 to 9 in the fields of aerospace, automobile, medical equipment and 3C digital.
